Coordination of Closed-Loop Supply Chain with Dual-Source Supply and Low-Carbon Concern - Jing Li; Shuying Gong (Complexity)
Considering the impact of dual-source supply and low-carbon manufacturing on a closed-loop supply chain (CLSC) system, this article constructs a CLSC model with two competitive dominant upstream suppliers and one following a downstream (re-)manufacturer, then coordinates supply chain through cost-sharing contract. Based on the industrial case in the area of power battery, we analyze the optimal strategies under competition, cooperation, and coordination structures separately and then investigate the influences of emission reduction effort and collection efficiency on supply chain performance. The results reveal that collection of used products can positively affect the (re-)manufacturer’s profit but has opposite impact on the new component supplier. Besides, recycling is beneficial to both low-carbon consumers’ utility and social welfare, but hurts the total profit of CLSC because of the high investment cost of collection. Therefore, the paper designs a cost-sharing contract, which is of applicability and efficiency for both economic and environmental development. Furthermore, it can also increase the profit of CLSC up to cooperation case and improve each member’s profit, eliminating double marginal effect and achieving supply chain coordination.